Improving the accuracy of predicting the hazard of the earth’s surface failure formation during underground mining of mineral deposits - Imansakipova, Botakoz; Aitkazinova, Shynar; Sakabekov, Auzhan; Shakiyeva, Gulim; Imansakipova, Meruyert; Taukebayev, Omirzhan (Dnipro University of Technology, 2021)
Purpose. Development of a new approach to improving the accuracy of predicting situations in which the earth’s surface failures occur as a result of undermining a rock mass during the development of mineral deposits. Methods. The critical situations, including the earth’s surface failures, are predicted on the basis of assessing the value of geoenergy and studying its change as large volumes of rock mass are involved in mining. Analytical solutions based on the fundamental laws of physics and mechanics of continuous media are used. The research is performed using methods of cause-and-effect analysis. Findings. Based on the cause-effect relationship, determined between the change in the value of the mass geoenergy and deformation processes on the daylight surface of the field, an effective method has been developed for ranking it according to the degree of hazard of failure formation with the simultaneous use of two criteria. One of the criteria is determined by the relative change in geoenergy during the system transition from the initial (stable) state to the current one, which becomes unstable under certain conditions. The second criterion is formed on the basis of the change in geoenergy during the transition from the current (possibly unstable) state to the final (stable) state. Originality. For the first time, when zoning the daylight surface of a field according to the degree of hazard of failure formation, two ranking criteria are used simultaneously, based on the assessment of geoenergy accumulated in a heterogeneous mass, when it is undermined in the conditions of triaxial compression. Practical implications. The territory ranking method, developed on the basis of the used criteria for hazard of failure formation, allows improving the quality of situational control, predicting risk situations and their development, as well as optimizing the short-term and long-term plans for the development of mining operations.

Мета. Розробка нового підходу до підвищення точності прогнозу ситуацій, за яких внаслідок підробки породного масиву при вийманні корисних копалин виникають провали земної поверхні. Методика. Прогноз критичних ситуацій, у тому числі провалів земної поверхні, виконується на основі оцінки величини геоенергії та дослідження її зміни у міру залучення у відпрацювання великих обсягів гірничої маси. Використані аналітичні рішення, що базуються на фундаментальних законах фізики та механіки суцільних середовищ. Дослідження виконувались із використанням методів причинно-наслідкового аналізу. Результати. На основі встановлення причинно-наслідкового зв’язку між зміною величини геоенергії масиву та деформаційними процесами на денній поверхні родовища розроблено ефективний метод її ранжування за ступенем провалонебезпеки одночасно за двома критеріями. Один із критеріїв визначається відносною зміною геоенергії при переході з початкового (стійкого) стану системи в поточний, який у певних умовах стає нестійким. Другий критерій формується на основі зміни геоенергії при переході з поточного (можливо нестійкого) стану в кінцевий (стійкий). Наукова новизна. Вперше при районуванні денної поверхні родовища за рівнем провалонебезпеки використовуються одночасно два критерії ранжирування, засновані на оцінці геоенергії, що накопичується в неоднорідному масиві в міру його підробки в умовах всебічного стиску. Практична значимість. Метод ранжування територій, розроблений на основі використання критеріїв провалонебезпеки, дозволяє підвищити якість ситуаційного контролю, прогнозу ризикових ситуацій та їх розвитку, оптимізувати короткостроковий та довгостроковий плани розвитку гірничих робіт.

Цель. Разработка нового подхода к повышению точности прогноза ситуаций, при которых вследствие подработки породного массива при выемке полезного ископаемого возникают провалы земной поверхности. Методика. Прогноз критических ситуаций, в том числе провалов земной поверхности, выполняется на основе оценки величины геоэнергии и исследования ее изменения по мере вовлечения в отработку больших объемов горной массы. Использованы аналитические решения, базирующиеся на фундаментальных законах физики и механики сплошных сред. Исследования выполнялись с использованием методов причинно-следственного анализа. Результаты. На основе установления причинно-следственной связи между изменением величины геоэнергии массива и деформационными процессами на дневной поверхности месторождения разработан эффективный метод ее ранжирования по степени провалоопасности одновременно по двум критериям. Один из критериев определяется относительным изменением геоэнергии при переходе из начального (устойчивого) состояния системы в текущее, которое в определенных условиях становится неустойчивым. Второй критерий формируется на основе изменения геоэнергии при переходе из текущего (возможно неустойчивого) состояния в конечное (устойчивое). Научная новизна. Впервые при районировании дневной поверхности месторождения по степени провалоопасности используются одновременно два критерия ранжирования, основанные на оценке геоэнергии, накапливаемой в неоднородном массиве по мере его подработки в условиях всестороннего сжатия. Практическая значимость. Метод ранжирования территорий, разработанный на основе использования критериев провалоопасности, позволяет повысить качество ситуационного контроля, прогноза рисковых ситуаций и их развития, оптимизировать краткосрочный и долгосрочный планы развития горных работ.
Keywords: failure formation hazard; zone regionalization; prediction; criterion; geoenergy; elastic deformation; ranking